Editorial: methods and protocols in brain stimulation - Carvalho, Sandra (2023)
The use of non-invasive brain stimulation (NIBS) techniques to study the brain has increased significantly in recent decades. It has become one of the most accepted therapeutic approaches and powerful tools in treating neurological and psychiatric disorders. NIBS, such as Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS), have been proven effective in several clinical conditions, such as major depressive disorders, stroke, and to improve addition/craving and cognition, in both young and geriatric populations (Yavari et al., 2016; Lefaucheur et al., 2020; Fregni et al., 2021; Teixeira-Santos et al., 2022). However, methods and protocols of brain stimulation are very heterogeneous and further research is needed to fine tune the modulatory effects of NIBS in the brain. In this research topic of methods and protocols of brain stimulation, five original research articles address various protocols of NIBS, such a study protocol for geriatric depression, a perspective article on how to test the association between baseline performance and effects of NIBS, and clinical trials discussing methods of brain stimulation on stroke and sleep quality.